From Strangers to Neighbors: Post-Disaster Resettlement and Community Building in Honduras - Alaniz, Ryan (University of Texas Press, 2017)
Natural disasters, the effects of climate change, and political upheavals and war have driven tens of millions of people from their homes and spurred intense debates about how governments and nongovernmental organizations (NGOs) should respond with long-term resettlement strategies. Many resettlement efforts have focused primarily on providing infrastructure and have done little to help displaced people and communities rebuild social structure, which has led to resettlement failures throughout the world. So what does it take to transform a resettlement into a successful community? This book offers the first long-term comparative study of social outcomes through a case study of two Honduran resettlements built for survivors of Hurricane Mitch (1998) by two different NGOs. Although residents of each arrived from the same affected neighborhoods and have similar demographics, twelve years later one resettlement wrestles with high crime, low participation, and low social capital, while the other maintains low crime, a high degree of social cohesion, participation, and general social health. Using a multi-method approach of household surveys, interviews, ethnography, and analysis of NGO and community documents, Ryan Alaniz demonstrates that these divergent resettlement trajectories can be traced back to the type and quality of support provided by external organizations and the creation of a healthy, cohesive community culture. His findings offer important lessons and strategies that can be utilized in other places and in future resettlement policy to achieve the most effective and positive results.